(untitled) (Revista Brasileira de Contabilidade e Gestão, 2021)
The main interests aroused in this work were the application of more effective technologies to improve the wood-adhesive interaction in glued panels, guaranteeing dimensional stability, thus ensuring the quality of products used in Pinusfurniture generated from EGP (Edge Glued Panel -panel with side glue). Aiming to evaluate the strength and wood-adhesive interaction of the glue line in EGP wood panels of Pinuselliottiiand Pinustaedalaterally glued with an adhesive based on polymeric isocyanate emulsion (EPI). In the production of joints of wooden parts, different machining processes were used (moulding machine, sandpaper and saw), parts with moisture contents (8 and 15%) and dimensions (slats with thickness 45 and 60 mm). The physical properties of the wood species of the bonded elements were evaluated, evaluating lateral bonding and end bonding through end joints (finger joint). The anatomical analyzes showed that the two Pinusspecies did not present significant differences between them (p˂0.05), and that factors such as wood density and moisture content of the studied slats did not influence the mechanical properties of the panels. The shear strength of P. elliottiiand P. taedaspecies were 137.03 kgf/cm2and 149.36 kgf/cm2, respectively. The highest tensile strength of finger jointseams, (262.64 kgf/cm2) was obtained by bonding the species and P. taeda. Analyzing the requirements of the standards, all species met the minimum values required for both wood failure and mechanical strength.